Optimasi Formula dan Evaluasi Stabilitas Sediaan Toner Wajah Ekstrak Daun Keji Beling (Strobilanthes crispus L.) - Alia Afrilia Gobel; Rizky Resvita Bahi; Moh. Rivaldi Mappa (Journal of Pharmaceutical and Sciences, 2025)
Facial skin is prone to dryness due to UV radiation, which accelerates premature aging (photoaging) and triggers various skin problems such as atopic dermatitis. In Indonesia, the prevalence of dry skin reaches 50%–80%. Several commercial toner products still contain alcohol, which can further dry the skin when used for a long period of time. Therefore, natural ingredients with moisturizing effects are needed, one of which is Strobilanthes crispus (keji beling) leaves, containing flavonoids with antioxidant activity. This study aimed to determine the effect of varying concentrations of Tween 80 surfactant on the stability of toner formulations. The research method was experimental, formulating four formulas with surfactant concentrations of 0% (F0), 5% (FI), 7.5% (FII), and 10% (FIII), followed by stability testing using the cycling test and evaluating organoleptic properties, homogeneity, viscosity, pH, irritation, and hedonic acceptance. The organoleptic evaluation showed that FI, FII, and FIII produced clear yellowish-green liquid preparations with a characteristic odor of keji beling leaves, whereas F0 produced a dark green liquid with the same odor. All formulas were homogeneous with a pH of 5. The viscosity values were 1.72 cPs for FI, 1.82 cPs for FII, 2.37 cPs for FIII, and 1.35 cPs for F0. Irritation testing showed negative results for all formulas, indicating no signs of primary irritation. Hedonic testing revealed that FIII was the most preferred by panelists. Based on these findings, it can be concluded that the formula containing 10% polysorbate (FIII) provided the best physical stability and panelist acceptance. Thus, variation in surfactant concentration affects the physical stability of Strobilanthes crispus leaf extract toner formulations.